2008
DOI: 10.1088/0953-8984/20/20/204121
|View full text |Cite
|
Sign up to set email alerts
|

Motion of ferroparticles inside the polymeric matrix in magnetoactive elastomers

Abstract: Ferroelastic composites are smart materials with unique properties including large magnetodeformational effects, strong field enhancement of the elastic modulus and magnetic shape memory. On the basis of mechanical tests, direct microscopy observations and magnetic measurements we conclude that all these effects are caused by reversible motion of the magnetic particles inside the polymeric matrix in response to an applied field. The basic points of a model accounting for particle structuring in a magnetoactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
177
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(191 citation statements)
references
References 11 publications
11
177
1
2
Order By: Relevance
“…[20] demonstrate that the chain-like aggregates of closely situated particles stimulate elongation of the ferrogels in the field direction. Therefore the results of experiments [16,22] and computer simulations [16,20,22] are in agreement with the conclusion of the presented model.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…[20] demonstrate that the chain-like aggregates of closely situated particles stimulate elongation of the ferrogels in the field direction. Therefore the results of experiments [16,22] and computer simulations [16,20,22] are in agreement with the conclusion of the presented model.…”
Section: Resultssupporting
confidence: 87%
“…However in experiments, where the chains of the densely situated particles took place, only elongation of the samples has been detected [16,22]. At the same time computer simulations of Ref.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The combination of magnetic and elastic properties leads to various phenomena which can be initiated by the external magnetic field [1][2][3][4][5][6][7]. These phenomena have opened up new possibilities for technological applications, such as: 1) magnetoelastic composites; with particles made of magnetostrictive hard or soft ferromagnetic material; 2) magnetorheological elastomers, for applications in the aerospace and automotive industries as actuators on antifriction components; 3) heat-shrinkable elastic ferromagnets with variable magnetic and conductive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the observed reinforcing effect of magnetic fillers have approached the problem from a magnetomechanical point of view, and investigated the microscopic properties through study of the magneto-elastic responses of the composity [1][2][3][4]. Less well understood, however, are the effects of the interactions between the filler and the surrounding polymer on submicroscopic length scales.…”
Section: Introductionmentioning
confidence: 99%